Parenting Styles and Its Influence on the Self-Help Skills of Kindergarten Learners in a Public School - Pamela Joie T. Sobrebiga; Sharon Rose G. Medez (Philippine Social Science Journal, 2021)
Using descriptive-comparative-correlational research, the study aimed to determine the parenting styles based on Baumrind's Parenting Typology and level of self-help skills of kindergarten learners using the Philippine Early Childhood Development Checklist. The dominant parenting style employed by the parents was authoritative when they were taken as a whole and grouped according to sex, employment status, and family monthly income except for the 6,000-10,000Php earners and the single parents who were authoritarian. The learners had slightly advanced development when taken as a whole and grouped according to the aforementioned variables except those raised by guardians who had average development. There was no significant difference in the self-help skills of the learners when they were grouped according to sex, monthly family income, and employment status. However, there was a significant difference when they were grouped according to the marital status of their parents. Lastly, there was no significant relationship between parenting styles and the self-help skills of learners.